2002
DOI: 10.1073/pnas.231608898
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting transcription factor binding site clustering to identify cis-regulatory modules involved in pattern formation in the Drosophila genome

Abstract: A major challenge in interpreting genome sequences is understanding how the genome encodes the information that specifies when and where a gene will be expressed. The first step in this process is the identification of regions of the genome that contain regulatory information. In higher eukaryotes, this cis-regulatory information is organized into modular units [cis-regulatory modules (CRMs)] of a few hundred base pairs. A common feature of these cis-regulatory modules is the presence of multiple binding sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
474
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(486 citation statements)
references
References 54 publications
7
474
0
2
Order By: Relevance
“…We also found an increased number of Twist motifs around individual instances of the Twist sequence motif that were bound compared with motif instances that were not bound (up to twofold enrichment, p # 2.032 3 10 À127 ), suggesting that TF binding sites often contain several copies of the TF's motif (Berman et al 2002). Additionally, motifs for Snail-an important Twist partner TF (Zeitlinger et al 2007)-were also enriched close to bound Twist motifs as observed previously (Sandmann et al 2007;Zeitlinger et al 2007).…”
Section: Identifying the Cis-regulatory Requirements Of Individual Bisupporting
confidence: 79%
“…We also found an increased number of Twist motifs around individual instances of the Twist sequence motif that were bound compared with motif instances that were not bound (up to twofold enrichment, p # 2.032 3 10 À127 ), suggesting that TF binding sites often contain several copies of the TF's motif (Berman et al 2002). Additionally, motifs for Snail-an important Twist partner TF (Zeitlinger et al 2007)-were also enriched close to bound Twist motifs as observed previously (Sandmann et al 2007;Zeitlinger et al 2007).…”
Section: Identifying the Cis-regulatory Requirements Of Individual Bisupporting
confidence: 79%
“…Sequence analysis of the eve gene indicates that there are more high-affinity Knirps binding sites within the eve stripe 3/7 element than in the 4/6 enhancer, consistent with relative sensitivities of these elements that we determined experimentally (Fig. 3) (Papatsenko et al, 2002;Berman et al, 2002). Removal of some of the Knirps binding sites in the eve stripe 3/7 enhancer reduces the sensitivity of this element to the Knirps gradient (Clyde et al, 2003).…”
Section: Setting Thresholdssupporting
confidence: 76%
“…However, the number of predicted high-affinity binding sites alone is not sufficient information to predict relative sensitivity to Knirps. If it were, one would expect the eve stripe 2 enhancer, with three predicted Knirps sites, to be more sensitive to Knirps than eve stripe 4/6, with only a single site, yet the reverse is true (Berman et al, 2002) (Fig. 3).…”
Section: Setting Thresholdsmentioning
confidence: 99%
“…TF motifs have been used to produce a genomewide map of TF binding sites [139], and predicting CRMs based on their higher densities has been shown to be beneficial [140][141][142][143]. If the identity of TFs active in the cell type of interest and their motifs is known, the predictive power of the methods increases for that cell type [144][145][146][147][148][149][150]. In a complementary approach, the loci of genes with a similar function can be searched for common TF binding sites [151][152][153][154].…”
Section: Human Tsssmentioning
confidence: 99%